Effect of gamma irradiation on structural, morphological and optical properties of thermal spray pyrolysis deposited CuO thin film. Issue 3 (1st February 2021) - Sarker, Pooja; Sen, Sapan Kumar; Mia, M.N.H.; Pervez, M.F.; Mortuza, A.A.; Hossain, Sazzad; Mortuza, M.F.; Ali, M.H.; Nur, Salahuddin; Kabir, Humayun; Chowdhury, M.A.M.
Abstract: This study reports the influences of gamma irradiation (GI) in the range of 20–100 kGy on CuO thin films via thermal spray pyrolysis technique on the glass substrates. The results demonstrate significant influences of GI on the crystallographic, microstructural and optical characteristics of CuO thin films. The obtained XRD results showed that the crystallinity of the films deteriorates by gradually decreasing crystallite size (from 59.13 to 46 nm) as applied gamma doses increases. However, the basic monoclinic crystal structure remains same. The dislocation density and lattice strain increased with the rise of GI absorbed dose due to the creation of defects. The values of number of crystallites per unit surface area increased as dose increased indicating the abundance of crystallization of nano CuO thin films. A UV–Vis–NIR spectrophotometer was utilized to determine the optical properties and obtained results indicated that the optical energy band gap (OBG) energies reduced from 2.00 to 1.72 eV as the doses increased from 0 to 100 kGy. No distinctions of the monoclinic phase of virgin CuO thin film have been perceived under applied absorbed doses, notwithstanding the slight deterioration of the crystallinity and narrowing the OBG.